Tetanus (Colombia Medica, 1988)
Tetanus is an infectious disease produced by a neurotoxin, tetanospasmin of Clostridium tetani, which acts at the myoneural plaque, brain gangliosides, and spinal cord, causing a picture of severe muscular spasm, with trismus in 75% of cases. As in first manifestations, there can be a serious generalized picture with a poor prognosis and a high mortality, especially if there is involvement of the ANS. The diagnosis is clinical, and there is no specific laboratory test. Prophylaxis through vaccination is effective in almost 10% of cases.